Neurofeedback Training to Improve Neuronal Regulation in ADD : A case report - Norsiah, Fauzan; Nazaruddin, Muhamad Sophian (Elsevier, 2012)
This report details the use of Neurofeedback training (NFT) on a 15 years old girl with Attention Deficit Disorder. The child’s mother reported a history of hyperactivity, inability to self-regulate/focus attention, impulsivity, self injury and behaviorally disinhibition. The goal was to enable the child to achieve a better brain regulation, leading to improvements in attention, mood, and social behavior. The sensors were placed on the scalp and connected to the computer software that detects specific neuronal activity. The subject showed an improvement in emotional reaction, a reduction in self injuries and oppositional behavior, and a better social relationship.